Economists at war : how a handful of economists helped win and lose the World Wars - Bollard, Alan (Oxford scholarship online., 2020)
Wartime is not just about military success. This text tells a different story - about a group of remarkable economists who used their skills to help their countries fight their battles during the Chinese-Japanese War, Second World War, and the Cold War.